Ustekinumab and Vedolizumab Dual Biologic Therapy in the Treatment of Crohn’s Disease - Eddie Y. Liu; Dustin E. Loomes (Case Reports in Medicine)
We present a case of refractory ileocolonic Crohn’s disease in a 27-year-old female treated with dual ustekinumab and vedolizumab biologic therapy. She had mucosal healing for the first time in 13 years after a 10-month treatment of ustekinumab overlapped with 6 months of vedolizumab. No side effects were observed during the 6 months of dual biologic therapy. Short-term dual biologic therapy may be considered as a treatment option for induction of remission in refractory cases of Crohn’s disease.